Tetragonia tetragonioides Protected against Memory Dysfunction by Elevating Hippocampal Amyloid-β Deposition through Potentiating Insulin Signaling and Altering Gut Microbiome Composition - Kim, Da Sol (Int J Mol Sci, 2020)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease. Herbal medicine may provide efficacious treatments for its prevention and/or cure. This study investigated whether a 70% ethanol extract of Tetragonia tetragonioides Kuntze (TTK; New Zealand spinach) improved the memory deficit by reducing hippocampal amyloid-β deposition and modulating the gut microbiota in rats with amyloid-β(25–35) infused into the hippocampus (AD rats) in an AD animal model. The AD rats had cellulose (AD-CON) or TTK (300 mg/kg bw; AD-TTK) in their high-fat diets for seven weeks. Rats with amyloid-β(35–25) infused into the hippocampus fed an AD-Con diet did not have memory loss (Normal-Con). AD-TTK protected against amyloid-β deposition compared to AD-Con, but it was higher than Normal-Con. AD-TTK protected against short-term and special memory loss measured by passive avoidance, Y maze, and water maze, compared to AD-Con. Compared to the Normal-Con, AD-Con attenuated hippocampal pCREB → pAkt → pGSK-3β, which was prevented in the AD-TTK group. Brain-derived neurotrophic factor (BDNF) and ciliary neurotrophic factor (CNTF) mRNA expression decreased in the AD-CON group, and their expression was prevented in the AD-TTK group. Hippocampal TNF-α and IL-1β mRNA expressions were higher in the AD-Con group than in the Normal-Con, and AD-TTK groups protected against the increase in their expression. The AD-CON group showed an increase in insulin resistance compared to the Normal-Con group and the AD-TTK group showed improvement. AD-Con separated the gut microbiome community compared to the Normal-Con group and AD-TTK overlapped with the normal-Con. The AD-Con group had more Clostridiales, Erysipelotrichales, and Desulfovibrionales than the AD-TKK and Normal-Con group but fewer Lactobacilales and Bacteroidales. In conclusion, the 70% ethanol extract of TTK enhanced the memory function and potentiated hippocampal insulin signaling, reduced insulin resistance, and improved gut microbiota in amyloid-β-infused rats.